2011
DOI: 10.1007/s10753-011-9352-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine Ameliorates l-Arginine-Induced Acute Pancreatitis in Rats

Abstract: The aim of this study was to determine whether oxymatrine has a protective effect against acute pancreatitis (AP) in a rat model of L-arginine-induced AP. AP was induced by two intraperitoneal injections of L-arginine (250 mg/100 g) at a 1-h interval. Oxymatrine (50 mg/kg) was administered every 6 h after the induction of AP. Oxymatrine significantly reduced the plasma amylase, D-lactic acid and tumor necrosis factor alpha concentration, serum diamine oxidase and lipase activity, and pancreatic myeloperoxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
1
18
0
1
Order By: Relevance
“…Our results are in agreement with previous studies showing anti-inflammatory effects of OM in other diseases. For example, Zhang et al (11) have demonstrated that OM effectively reduces the serum TNF-α level in rats with L-arginine-induced acute pancreatitis. It has also been shown that OM is able to reduce neuronal cell apoptosis by inhibiting Toll-like receptor 4/nuclear factor κ-B-dependent inflammatory responses in traumatic rat brain injury (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in agreement with previous studies showing anti-inflammatory effects of OM in other diseases. For example, Zhang et al (11) have demonstrated that OM effectively reduces the serum TNF-α level in rats with L-arginine-induced acute pancreatitis. It has also been shown that OM is able to reduce neuronal cell apoptosis by inhibiting Toll-like receptor 4/nuclear factor κ-B-dependent inflammatory responses in traumatic rat brain injury (14).…”
Section: Discussionmentioning
confidence: 99%
“…(Kushen) that has been approved by the State Food and Drug Administration of China for treating hepatitis B (7,8). Cumulative evidence has suggested that OM possesses multiple biological and pharmacological properties, such as anti-inflammatory (9)(10)(11), antitumor (12,13), anti-apoptotic (14), antifibrotic (15), antioxidant (16), and antiarrhythmic activities (17). Chen et al (18) demonstrated that…”
Section: Introductionmentioning
confidence: 99%
“…Recently, extensive experimental studies on OM have been performed to extend its applications to the treatment of cancer (Zhang et al , ; Guo et al , ), lung ischemia reperfusion injury (LIRI) (Zhu et al , ), heart diseases (Hong‐Li et al , ; Cao et al , ; Li et al , ; Wang et al , ), pancreatic diseases (Zhang et al , ), and skin diseases (Fan et al, ), as well as applications in neuroprotection (Xu et al , ) and analgesia (Liu et al , ). Specifically, OM exhibits a variety of effects that can prevent tumor development in human gastric cancer (Guo et al , ), human breast cancer (Zhang et al , ), human liver cancer (Song et al , ), laryngeal carcinoma (Ying et al , ), gallbladder cancer (Wu et al , ), and human pancreatic cancer (Chen et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental and clinical patho-physiology of AP is poorly understood [13]. Therefore, AP is associated with high morbidity and mortality rates ranging from 15% to 40% in its severe form [45]. L-arginine (L-arg) is an amino acid necessary for the body to make proteins.…”
mentioning
confidence: 99%